(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2025)
“Peace for resources”: US strategy in the Central African Great Lakes Region (1994-2025) On June 27, 2025, foreign ministers of Rwanda and Democratic Republic of Congo (DRC) signed a peace treaty in Washington, in the presence of the US President Donald Trump, aimed at ending decades of devasting conflict between the two neighbors. In the background of US mediation, there is what could be named a “commercial diplomacy” that considers the strategic interests of the Trump administration in the Region as the main reasons behind his diplomacy. However, Washington’s engagement in the peace process between Rwanda and DRC seems quite controversial, considering the lacking – if not totally missing – activism that characterized US foreign policy in the region in the Nineties. By analyzing diplomatic documents available online at the National Security Archive and the Clinton Digital Library and secondary sources, this paper aims at retracing the evolution of US strategy in the Great Lakes Region, from the 1994-98 crisis to the current commitment in the peace process between the two States, in order to show how Washington’s strategic interests, and not the values of peace, democracy and rule of law, represent the driving force behind the President’s mediation and the United States’ presence in the region.